A descriptive study to assess the knowledge regarding breastfeeding among antenatal mothers in selected hospitals of Pune city - Shiroor, Geeta; Wankhede, Supriya; Wajage, Nikita; Wadkar, Priyanka (International Journal of Nursing Research, 2023)
“Mother’s milk, time tasted for millions of years, is the best nutrients for babies because it is Nature’s perfect food” Breastfeeding is the ideal form of feeding in the neonate. Artificial feeding exposes the infant to infection and results in over a million die annually worldwide due to its ill effects The Care for a child needs to begin is the first few hours of life with exclusive breastfeeding and appropriate interventions at 4-6 months in the form of timely complementary feeding. Therefore, breastfed babies have higher resistance to infection, such as respiratory viruses. Breast feeding, the most natural way of infant feeding to satisfy nutritional, metabolic and psychological needs of the baby. Breastfeeding contributes to the health and well-being of mothers; it helps to reduce the risk of ovarian cancer and breast cancer. \Aim: To assess the knowledge of Breastfeeding among antenatal mothers. To associate findings with selected demographic variables. Methods: Quantitative approaches with the Non-Experimental Descriptive design were used. All Primi-Gravida Mother with a sample size of 60 was collected in Bharati Hospital Research Centre Pune. A Structured Questionnaire was prepared for data collection. Results: The finding of the study was, 24% Mothers are having good knowledge, 35% Mothers are having the average knowledge, and 01% Mothers are having poor knowledge regarding Breastfeeding. Age, family pattern, family incomes are associated with the knowledge. Conclusion: Maximum mothers have average knowledge regarding breastfeeding.